FAKTOR YANG MEMPENGARUHI KONSERVATISME AKUNTANSI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Olvy Angela, Susanto Salim (Jurnal Paradigma Akuntansi, 2020)
The purpose of this study is to examine the analysis of factors affecting accounting conservatism of manufacture companies listed on the Indonesia Stock Exchange for the period 2016-2018. Samples were selected using 70 purposive sampling methods. Sample was selected using purposive sampling method amounted to 61 companies. This study uses multiple regression analysis methods helped by Microsoft Excel and IBM SPSS 23. This study shows that simultaneously financial distress, leverage, investment opportunity set (IOS), managerial ownership, and firm size have a significant effect on accounting conservatism. Partially, financial distress and leverage have a significant negative effect on accounting conservatism. The investment opportunity set (IOS), managerial ownership and firm size have no significant effect on conservative accounting.